The role of early life nutrition in the establishment of gastrointestinal microbial composition and function. (4th March 2017) - Davis, Erin C.; Wang, Mei; Donovan, Sharon M.
ABSTRACT: The development of the human infant intestinal microbiota is a sequential process that begins in utero and continues during the first 2 to 3 years of life. Microbial composition and diversity are shaped by host genetics and multiple environmental factors, of which diet is a principal contributor. An understanding of this process is of clinical importance as the microbiota acquired in early life influence gastrointestinal, immune and neural development, and reduced microbial diversity or dysbiosis during infancy is associated with disorders in infancy and later childhood. The goal of this article was to review the published literature that used culture-independent methods to describe the development of the gastrointestinal microbiota in breast- and formula-fed human infants as well as the impact of prebiotic and probiotic addition to infant formula, and the addition of solid foods.